2016
DOI: 10.18034/mjmbr.v3i2.412
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping System of Maize with Different Winter Vegetables

Abstract: The experiment was conducted at farmers’ fields of Hqripur in Dauadkandiupzilla underOn- Farm Research Division of Bangladesh Agricultural Research Institute, Comilla during the rabi seasons of 2012-13 and 2013-14 toevaluate the performance of maizeunder intercropping with different winter vegetables. The experiment comprised of four treatments viz., Maize + Spinach, Maize + Red amaranth, Maize + Coriander and Sole maize with four replications. Results revealed that each of maize- vegetables intercropping comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
(10 reference statements)
8
3
0
Order By: Relevance
“…The lower relative yield of maize in intercropping indicated that the crop faced competition for space, nutrients, light, and water. The findings are in agreement with that of Hossain et al (2015).…”
Section: Relative Yieldsupporting
confidence: 91%
“…The lower relative yield of maize in intercropping indicated that the crop faced competition for space, nutrients, light, and water. The findings are in agreement with that of Hossain et al (2015).…”
Section: Relative Yieldsupporting
confidence: 91%
“…With respect to leaf area index the sole sweet corn (60 cm × 20 cm) which recorded the higher leaf area index (0.43,1.69 and 4.71 at 20, 40 and 60 DAS, respectively) as compared to sweet corn (60 cm × 20 cm) + spinach (1:1) intercropping system (0.29, 1.16 and 3.20 at 20, 40 and 60 DAS, respectively) (Table 2). These results corroborate the findings of Hossain et al, (2015) and Chaudhari et al, (2018). Plant canopies intercept light with varying degrees of efficiency associated chiefly with the LAI.…”
Section: Growth Attributessupporting
confidence: 92%
“…The increase in fresh cob yield was 50.5 percent over the intercropping of spinach at 1:1 row proportion with sweet corn sown at 60 cm inter row spacing (Table 3). The increment in the fresh cob yield of sweet corn was due to higher yield attributing characteristics viz., cob length, cob girth, cob weight and number of kernels per cob, these results are in line with the findings of Hossain et al, (2015).…”
Section: Yield and Yield Attributessupporting
confidence: 91%
“…Similar results were observed by researchers Rahaman, et al, 2015 andHossain, et al, 2015. The lowest maize equivalent yield (9.53 t ha -1 ) was obtained from maize + red amaranth intercrop combination.…”
Section: Relative Yieldsupporting
confidence: 89%
“…Higher gross return was obtained from all intercrop combinations than sole crop. Many researchers also documented higher gross margin or net return in intercropping system than sole crop (Ali, et al, 2015;Alam et al, 2008;Bhuiyan et al, 2013;Farhad et al, 2014;Rahaman, et al, 2015 andHossain, et al, 2015). Among the combinations, the highest gross return was obtained from maize + potato intercropping system, which was 81% higher than sole maize.…”
Section: Monetary Advantagementioning
confidence: 98%